Transaksi Digital (e-commerce) Pada @ghanie_lee.shop Kediri Dalam Fatwa DSN-MUI No. 05/DSN-MUI/IV/2000 - Nafi’ah, Uswatun (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The large number of business people or shops in Indonesia who practice buying and selling without meeting in person or via the Internet is the inspiration for this research. Many of these businesses pay no attention to the formalities or legal requirements associated with buying and selling without a meeting. The reality of modern technology such as digital technology cannot be denied. This research aims to determine the acceptability of ordering transactions based on DSN-MUI Fatwa No. 05/DSN-MUI/IV/2000 and the role of digital transactions (e-commerce) in boosting product sales with a fast and simple transaction process. This research adopts descriptive methodology and qualitative research techniques. In-depth interviews, participant observation, and documentation were used as data collection strategies. Data reduction, data presentation, and concluding are all used in data analysis.